Effect of magnetic field on imbibition phenomenon in fluid flow through fractured porous media with different porous material - Gohil V. P. (Nonlinear Engineering, 2019)
In this paper, the counter-current Imbibition phenomenon is considered in a fractured heterogeneous porous medium with the consideration of different porous materials like fine sand, volcanic sand and glass beads and magnetic field effect. The Homotopy analysis method is used here to derive an expression for finding the saturation profiles in a fractured heterogeneous porous medium with and without considering the magnetic field effect. Simulation results are developed for the saturation profiles to study the effect of inclination and the viscosity variation of native fluids on the saturation rate and the recovery rate of the reservoir with some interesting choices of parameters.